Studies in paraconsistent logic ii: quantifiers and the unity of opposites (1985)
In this paper, the propositional logics introduced in a previous work (N.C.A. da Costa and R.G. Wolf, Studies in paraconsistent logic I: the dialectical principle of the unity of opposites, Philosophia 9(1980) ,pp.189-217) are extended to first-order predicate calculi. 0ur aim is to formalize certain aspects of dialectics, as they are interpreted by McGill and Parry (V.J. McGill and W.T. Parry, The unity of opposites: a dialectical principle, Science and Society 12(1948) ,pp.418-444).